Russian-Kazakhstan Borderland: from Administrative Borders of Kazakhstan in RSFSR to Modern State Borders - K. B. Korzhenevsky (Научный диалог, 2022)
The problems of the formation of the Russian-Kazakh border line are considered. An analysis of the current territorial claims and risks from neighboring states to the Russian Federation, as well as the current state of affairs in society, science and politics in relation to the Russian-Kazakh border is made. Information, confirmed by archival materials, is analyzed on the demarcation processes carried out in the Soviet period along the entire line of contact between the two states. The main factors that influenced the formation of borders are studied, as well as the complexity of the controversial issues and the existing ways to solve them are shown. It is concluded that the current state border between Russia and Kazakhstan was formed in the 1920s—1930s by leveling the vast majority of controversial issues, on the basis of their comprehensive consideration of various authorities. At the same time, the historically substantiated data presented in the article show the inconsistency of the current claims of the national elites of the Kazakh side, proving the historical legitimacy of the existing Russian-Kazakh border line. It is concluded that the state authorities of Russia and Kazakhstan do not raise the issue of borders, which contributes to maintaining stability in relations between the two states.